Value at risk estimation of exchange rate in banking industry - Siti Saadah; Marsiana Luciana Sitanggang (University of Merdeka Malang, 2020)
More integrated financial sector has made market risk arising from volatility of exchange rate critical for banking industry. In attempt to mitigate such risk, this study aims to measure risk from IDR/USD exchange rate movement using value-at-risk method by comparing results of estimates using standard and asymmetric generalized autoregressive conditional heteroscedasticity models. Using data on the daily exchange rate of IDR to USD between July 31, 2018 and July 31, 2019, this study found that the asymmetric exponential GARCH using generalized error distribution is the best approach to estimate exchange rate risk. Results of the estimate suggest that standard GARCH model generated a more conservative measure of risk than value-at-risk estimated using exponential GARCH model. Value at risk can be one of the risk indicators for risk managers in banks. The choice of a model is likely to depend on the attitude to risk itself. Risk averse character who does not like risk will choose the most conservative method in calculating the VaR. JEL Classification: E44, G4, G11DOI: https://doi.org/10.26905/jkdp.v24i4.4808